Lung metastasis induced chronic compartment syndrome of the lower leg - Vranjes, Miodrag; Lakić, Tanja (International Journal of Research in Orthopaedics, 2021)
Compartment syndrome occurs when the pressure within a defined compartmental space increases above a critical pressure threshold. Lung cancer is one of the world's most frequently diagnosed cancer whose metastases are rare cause of compartment syndrome. We present a 50 year old male patient who was admitted to our emergency department due to painful left lower leg, swelling and paresthesia of the medial side of the foot that lasted about 2 months back. The diagnosis of metastatic lung adenocarcinoma was set 9 months earlier. Physical examination revealed an ill-defined, tense, and tender swelling left calf and X-ray images confirmed periosteal reaction on all four cortices of both bones without osteolytic lesions. After an adequate laboratory analyses and preoperative preparation, debridement with biopsy and fasciotomy was performed. Histopathological evaluation showed necrotic tumor tissue that morphologically and immunohistochemically corresponds to lung cancer. We performed an above knee amputation and the next day, the patient was discharged home, due to his personal request.